Phylogenetic relationships of Afrobrunnichia Hutch. & Dalziel (Polygonaceae) based on three chloroplast genes and ITS (2009)
The subfamily Eriogonoideae (Polygonaceae) comprises 31 genera of which 20 are part of the radiation of Eriogonum and allied genera in North America. The eleven remaining genera are all woody, and include species that are vines, trees and shrubs. They are distributed in North, Central and South America, the Antilles and West Africa, and in most cases the number of species is not known, even less their relationships. Brunnichia is a woody vine native to the southeastern United States. In the past some authors have recognized species of Brunnichia as occurring in West Africa. Alternately, others recognized two genera, Brunnichia corresponding only to the American species and Afrobrunnichia to the African species. In this study two accessions of Afrobrunnichia erecta from Gabon and Ghana, representatives of Podopterus, Brunnichia ovata , and several other species of Polygonaceae are analyzed using three chloroplast genes (rbcL, matK, ndhF ) and the nuclear ribosomal internal transcribed spacer (ITS). Maximum parsimony and maximum likelihood analyses strongly support Afrobrunnichia as sister to the remaining genera of Eriogonoideae; Brunnichia and Antigonon are strongly supported as sister genera. Based on these results, Afrobrunnichia is supported as a separate genus from Brunnichia. Podopterus is placed sister to Coccoloba .